Anti-diabetic effects of ethyl acetate and n-butanol fractions of Acacia nilotica leaves methanolic extract on alloxan-induced diabetic wistar rats - Tanko Y.,Muhammad A.,Elaigwu, J Mohammed K.A.,Jimoh, A.,Sada N.M.,M.K Dallatu,Yerima M and Mohammed A (Journal of Applied Pharmaceutical Science, 2013)
Evaluation of hypoglycaemic activity of ethyl acetate and n-butanol fractions of Acacia nilotica on alloxan induced diabetic Wistar rats has been investigated. Two doses of the ethylacetate fraction 50 and 100 mg/kg was administered. As regard to 50mg/kg caused a significant (P
Keywords: Anti-diabetic,Alloxan,Ethylacetate,n-butanol Acacia nilotica.